Sustainability Dimensions of a North American Lentil System in a Changing World - Warne, Teresa; Ahmed, Selena; Byker Shanks, Carmen; Miller, Perry (Frontiers in Sustainable Food Systems, 2019)
Food production and consumption are among the largest drivers of global change. The adoption of lentil in production systems and in plant-based diets is a food system solution that can support the environmental, socio-economic, and human health dimensions of sustainability. The purpose of this study is to evaluate producer and consumer perceptions of the sustainability profile of the lentil system in Montana (USA), and the surrounding region that includes Idaho (USA), North Dakota (USA), Washington (USA), and Canada, in the context of global change. Surveys were conducted with lentil producers (n=63; conventional n=42, organic n=15, and mixed management n=6) and consumers (n=138) in the rural state of Montana (USA). The most prevalent agronomic reason for including lentil in production systems reported by producers is to diversify crop rotation (92%). The most prevalent economic reasons for including lentil in rotation reported by producers is to capitalize on dryland production (95%) and to serve as a cash crop (87%). With respect to lentil consumption, the most prevalent health-related perceptions were that eating lentils helps to improve nutrition (88%), feel satiated or full (85%), and support a plant-based diet (81%). Consumers and non-consumers of lentils alike reported they would increase lentil consumption based on environmental (78%), economic (75%), and health and nutrition (72%) information contrasting lentils and animal-based protein sources. Overall, findings highlight how lentil supports multiple dimensions of sustainability from perceptions of producers and consumers in Montana (USA), Idaho (USA), North Dakota (USA), Washington (USA), and Canada, and recognizes barriers and opportunities for promoting lentil in agricultural systems and plant-based diets. Impacts of market, policy, and climate change on lentil production, and lack of consumer knowledge on benefits of lentils to help meet food security through a sustainable diet, challenge sustainability dimensions of lentil in the food system.